2022
DOI: 10.1038/s41598-022-18152-5
|View full text |Cite
|
Sign up to set email alerts
|

Considering epitopes conservity in targeting SARS-CoV-2 mutations in variants: a novel immunoinformatics approach to vaccine design

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has gained mutations at an alarming rate in the past years. Developing mutations can increase the virus's pathogenicity and virulence; reduce the efficacy of vaccines, antibodies neutralization, and even challenge adaptive immunity. So, it is essential to identify conserved epitopes (with fewer mutations) in different variants with appropriate antigenicity to target the variants by an appropriate vaccine design. Yet as, 3369 SARS-CoV-2 genomes were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…Their study further identified conserved common neutralizing epitopes on the SARS-CoV-2, including YLTPGDSSSGWTAGAAAYYV (247–267 aa), TFKCYGVSPTKLNDL (376–390 aa) on S1 and LNEVAKNLNESLIDLQELGK (1186–1205 aa) on the S2 [ 116 ]. A recent immunoinformatic study predicted conserved and highly immunogenic CTL-induced epitopes on S1 VRFPNITNL (327–335 aa) and PYRVVVLSF (507–515 aa) ( Table 1 ), while the CTL-induced epitopes on S2 were identified to be VVFLHVTYV (1060–1068 aa) and GVVFLHVTY (1059–1067 aa) ( Table 2 ) [ 117 ]. Based on the conservancy, antigenicity, allergenicity, population coverage and transmembrane location, another study chose potential conserved epitopes from the S1 (FNATRFASVYAWNRK, 342–356 aa) ( Table 1 ), S2 (FLHVTYVPAQEKNFT, 1062–1072 aa) ( Table 2 ) and the E/M protein to construct a SARS-CoV-2 vaccine and revealed that it had high immunogenicity and broad neutralizing activity against the SARS-CoV-2 RBD ( Figure 3 ) [ 118 ].…”
Section: Sars-cov-2 S Conserved Regions As a Potential Target For Vac...mentioning
confidence: 99%
“…Their study further identified conserved common neutralizing epitopes on the SARS-CoV-2, including YLTPGDSSSGWTAGAAAYYV (247–267 aa), TFKCYGVSPTKLNDL (376–390 aa) on S1 and LNEVAKNLNESLIDLQELGK (1186–1205 aa) on the S2 [ 116 ]. A recent immunoinformatic study predicted conserved and highly immunogenic CTL-induced epitopes on S1 VRFPNITNL (327–335 aa) and PYRVVVLSF (507–515 aa) ( Table 1 ), while the CTL-induced epitopes on S2 were identified to be VVFLHVTYV (1060–1068 aa) and GVVFLHVTY (1059–1067 aa) ( Table 2 ) [ 117 ]. Based on the conservancy, antigenicity, allergenicity, population coverage and transmembrane location, another study chose potential conserved epitopes from the S1 (FNATRFASVYAWNRK, 342–356 aa) ( Table 1 ), S2 (FLHVTYVPAQEKNFT, 1062–1072 aa) ( Table 2 ) and the E/M protein to construct a SARS-CoV-2 vaccine and revealed that it had high immunogenicity and broad neutralizing activity against the SARS-CoV-2 RBD ( Figure 3 ) [ 118 ].…”
Section: Sars-cov-2 S Conserved Regions As a Potential Target For Vac...mentioning
confidence: 99%
“…The conservity was checked by predicting epitopes with the help of immune epitope database (IEDB). This method provides a scientific approach for selecting epitopes with good immunogenicity and conservity against any virus 40 . Currently, immune system stimulation triggers allergic reaction in response to the vaccines developed.…”
Section: Discussionmentioning
confidence: 99%
“…Their study further identified conserved common neutralizing epitopes on the SARS-CoV-2 including YLTPGDSSSGWTAGAAAYYV (247-267 aa), TFKCYGVSPTKLNDL (376-390 aa) on S1 and LNEVAKNLNESLID-LQELGK (1186-1205 aa) on the S2 [106]. A recent immunoinformatic study predicted conserved and highly immunogenic CTL-induced epitopes on S1 VRFPNITNL (327-335 aa), and PYRVVVLSF (507 -515 aa) (Table 1), while the CTL-induced epitopes on S2 were identified to be VVFLHVTYV (1060-1068 aa) and GVVFLHVTY (1059-1067 aa) (Table 2) [107].…”
Section: Sars-cov-2 S Conserved Regions As a Potential Target For Vac...mentioning
confidence: 99%